ANALISIS PENGARUH JARINGAN, TEKNOLOGI INFORMASI DAN KOMUNIKASI, SERTA INOVASI TERHADAP KEUNGGULAN BERSAING DAN KINERJA USAHA (STUDI PADA UMKM DI PURWOKERTO) - Fahmi, Alif Khaidir Ali Fahmi; Mudiantono, Mudiantono (Diponegoro Journal of Management, 2019)
Micro, Small, and Medium Enterprises (MSMEs) in Purwokerto which is increasing is certainly very good, but it must also be balanced with good business performance. Then, it turns out that behind the increase there are eight problems that are often faced by MSMEs two of which are the low mastery and use of technology and narrow networks. This study aims to analyze the influence of network, Information dan Communication Technology (ICT), and innovation on competitive advantage and business performance. The population in this study is the owner of MSMEs in Purwokerto. The number of samples used was 100 respondents whose business has been established for more than one year. This research uses SEM analysis technique with AMOS 23. The results of this study show that network, ICT, and innovation have positive and significant effect on competitive advantge. Then, network, ICT, and innovation have positive and significant effect on business performance. Innovation have largest total influence and direct influence on competitive advantage. ICT have largest total influence and direct influence on business performance. Network is the second largest total influence and direct influence on business performance. Then, innovation have the largest indirect effect on business performance.